2008
DOI: 10.1117/12.795185
|View full text |Cite
|
Sign up to set email alerts
|

Design and optimization of plasmonic-based metal-dielectric nanocomposite materials for energy applications

Abstract: Metallic nanoparticles embedded in dielectrics permit enhanced capture of light at specific wavelengths through excitation of plasmons, i.e. the quanta of coherent and collective oscillations of large concentrations of nearly free electrons. In order to maximize the potential of such enhanced absorption in useful tasks, such as the generation of carriers in photocatalysts and semiconductors, it is important to be able to predict and design plasmonic nanocomposites with desired wavelength-dependent optical abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The PL and PLE spectra of the TiO 2 :N and TiO 2 :N mixtures with 0.5, 1 and 2 wt.%SiO 2 , Ag and Ag/SiO 2 , respectively, were recorded in the front-angle geometry at room temper ature (RT) using a Horiba Jobin Yvon Fluorolog-3 spectrofluorometer (model FL [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. For the PLE studies, the powders were irradiated time of 165 min (90 cycles of irradiation) with a 450 W Xe lamp, choosing an emission wavelength equal to 530 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PL and PLE spectra of the TiO 2 :N and TiO 2 :N mixtures with 0.5, 1 and 2 wt.%SiO 2 , Ag and Ag/SiO 2 , respectively, were recorded in the front-angle geometry at room temper ature (RT) using a Horiba Jobin Yvon Fluorolog-3 spectrofluorometer (model FL [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. For the PLE studies, the powders were irradiated time of 165 min (90 cycles of irradiation) with a 450 W Xe lamp, choosing an emission wavelength equal to 530 nm.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, considering the studies reported in the literature [9][10][11][12], doping with non-metals is quite encouraging to enhance the TiO 2 optical activity in the visible region. Among the metals used for doping TiO 2 , Ag has been widely used in recent years, due to the ability of the TiO 2 /Ag mixture to generate surface plasmons, which create an intense electric field that enhances the optical properties [5,6,[13][14][15][16][17], the ability to stabilize the non-metals dopants during the synthesis pathway [4] and for the efficiency of the electron-hole separation that promote the charge transfer processes [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The multimodal absorbing coating (B3) exhibited a relatively high absorptance of 0.866, which was higher than the conventional coatings with values of 0.803 (B1) and 0.825 (B2), respectively. As the nano-sized WC can offer significant potential as a material showing enhanced or tunable light harnessing [19][20][21][22], thus the absorptance of sample B2 was measured to be higher than that of sample B1. The enhancement in solar absorptance in the multimodal (B3) coating over the conventional (B1 and B2) coatings will be discussed in Section 4.…”
Section: Phases Analysismentioning
confidence: 99%
“…10,11 Despite the fact that some absorption enhancements have been demonstrated in various core-shell systems, [12][13][14] there has been no systematic study of the enhancement of the optical absorption of the substrate in a silicon solar cell.…”
Section: -2mentioning
confidence: 99%
“…23 Furthermore, only when the diameter of a NP is over 10 nm can it be assembled on different dielectric substrates using robust manufacturing techniques. 10 Therefore, Ag NPs whose diameters range from 10 to 100 nm are chosen to represent the actual synthesis results. For compatibility with experimental results, 8,[15][16][17][18][19] the Ag core diameter and the dielectric shell thicknesses are set to be less than 100 and 30 nm, respectively.…”
Section: Aip Advances 5 097129 (2015)mentioning
confidence: 99%